2016
DOI: 10.1111/apa.13438
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid levels were related to socio‐demographic characteristics in a German population‐based child cohort

Abstract: Adolescents with higher family wealth and social status showed a lower cardiovascular risk profile, as measured by the concentrations of HDL cholesterol and triglycerides as well as ApoA1 and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…The quantity of dietary cholesterol intake and serum lipid profiles may be affected by socio-economic factors [46, 47]. Our analysis provided such evidence that cholesterol/egg intakes and some serum cholesterol were not uniformly distributed across educational groups.…”
Section: Discussionmentioning
confidence: 72%
“…The quantity of dietary cholesterol intake and serum lipid profiles may be affected by socio-economic factors [46, 47]. Our analysis provided such evidence that cholesterol/egg intakes and some serum cholesterol were not uniformly distributed across educational groups.…”
Section: Discussionmentioning
confidence: 72%
“…This study provides an openly available R package including convenient functions to transform measurement values into SDS values for ALT, AST, and GGT. Regarding limitations, others have already reported that the composition of the LIFE Child cohort differs from the general distribution in the city of Leipzig, especially regarding the social background of the participants . Children from socially disadvantaged families were under‐represented in the LIFE Child study, possibly because of a less‐pronounced health awareness .…”
Section: Discussionmentioning
confidence: 94%
“…Regarding limitations, others have already reported that the composition of the LIFE Child cohort differs from the general distribution in the city of Leipzig, especially regarding the social background of the participants. (38) Children from socially disadvantaged families were under-represented in the LIFE Child study, possibly because of a less-pronounced health awareness. (39) Because of the ethnic composition of the city of Leipzig and under-representation of nonwhites, this study does not describe the potential influence of ethnicity on transaminases.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This suggested that the association between the only-child status and dyslipidemia may be partly dependent on these factors. It was suggested that triglycerides level was inversely associated with education and salary in some developed areas 34,35 . However, other studies found that individuals of lower socioeconomic status (SES) had lower levels of TC and LDL-C in developing areas 36,37 .…”
Section: Discussionmentioning
confidence: 99%